Diagnosis: What's in a Word? - Sanders, James T. (Canadian Journal of Counselling and Psychotherapy, 2012)
This article reviews the long-standing issue regarding the role and function of diagnosis within the counselling process. The controversy has traded upon the spectrum of functions assigned to diagnosis ranging from diagnosis as (1) a dynamic causal model of disease to (2) a descriptive summary statement _ of correlated symptomatology. It is argued that the irreconcilable positions taken by client-centered versus diagnostic counsellors have been largely sustained by the failure to resolve definitional ambiguities.